Winter Olympic Games in Lithuanian Media - Žičkevičiūtė - Ahmed, Evelina (Žurnalistikos tyrimai, 2023)
The Winter Olympics Games is the most important sports event which is reported in Lithuanian media. There are no researches which would show how Lithuanian sports journalists publicate news about Winter Games. The first task is to find out the concept of media, tthe functions and tasks of media, genres and titles of media texts. The second task is to discuss the Winter Olympics and sports media functions. The third task is to elucidate the models of agenda setting and framing theories. The fourth is to perform quantitative and qualitative analysis of content research. In order to implement the first, second and third tasks, an analytical descriptive method is used. In order to implement the fourth, the methods of quantitative and qualitative analysis of the content are used. The results of the research examining the relationship between agencies and authorial publications in the online news dailies Delfi.lt and Lrytas.lt published the most agency news. Sports journalists used the most used the interview genre – 116 times. It turned out that sports journalists mostly published news about Lithuanians competing in the Olympics, rather that foreign athletes. It became clear that sports journalists, when writing publications about Lithuanian athletes used expressive headlines at the Winter Olympics. Analyzing the tone of the presentation of expressive headlines, it became clear that mostly used the negative tone in their authorial publications about Lithuanian athletes.